Sexual Stereotypes Ascribed to Black Men Who Have Sex with Men: An Intersectional Analysis - Calabrese, Sarah K. (Arch Sex Behav, 2017)
Sexual stereotypes may adversely affect the health of Black MSM. Greater understanding of the nature and nuances of these stereotypes is needed. This online, survey-based study used an inductive, intersectional approach to characterize the sexual stereotypes ascribed to Black MSM by the U.S. general public, their distinctiveness from those ascribed to Black men and MSM in general, and their prototypicality relative to these broader groups. Members of the public, recruited in 2014–2015, were randomly assigned to one of five survey conditions, across which the social group with respect to whom they responded varied systematically by race (Black, White, or unspecified) and sexual orientation (gay, heterosexual, or unspecified). Participants (n=285) reported stereotypes of their assigned group that they perceived to exist in U.S. culture in an open-response format. Cross-condition comparisons revealed that, overall, Black gay male stereotypes were non-prototypical of Black men or gay men. Rather, stereotypes of Black men were more similar to Black heterosexual men and stereotypes of gay men were more similar to White gay men. Nonetheless, 11 of the 15 most frequently reported Black gay male stereotypes overlapped with stereotypes of Black men (e.g., large penis), gay men (e.g., deviant), or both (e.g., promiscuous). Four stereotypes were unique relative to both: down low, diseased, loud, and dirty. Findings suggest that Black MSM face multiple derogatory sexual stereotypes, several of which are group-specific. These stereotypes are consistent with cultural (mis)representations of Black MSM and suggest a need for more accurate portrayals of existing sexual diversity within this group.